Assessment of Novel Inorganic Storage Medium with Low Melting Point. (May 2015) - Pfleger, N.; Braun, M.; Eck, M.; Bauer, T.
Abstract: Thermal energy storage is essential to increase the efficiency of industrial processes by waste heat utilization and to enable future solar electricity generation by solar thermal power plants. Taking into account the need to reduce the emission of CO2 and to save conventional energy both processes are indispensable. However with the (direct) storage media used so far the range of applications is limited. Currently organic media are used whichare not appropriate at high temperatures due to high vapor pressures, low flash points and low thermal stabilities. Those challenges can be tackled by using inorganic media. Yet applications are limited so far because state of the art inorganicstorage materials cannot be used below 100  C requiring expensive anti-freeze systems. This paper presents a novel storage medium combining advantages of both organic media and state of the art inorganic media. This storage medium was developed by a novel method[1] and was assessed by the investigation of the most essential thermal properties, such as the heat capacity, viscosity, phase diagram around the eutectic point as well as the thermal stability. To get an idea about the thermal stability, state of the art TGA measurements were performed which suggested a higher thermal stability as compared to organic media.